The Endangered Species Act: Interfacing with Agricultural and Natural Ecosystems - McGaughey, Bernalyn; Anderson, Lars W. J.; Bodenchuk, Michael J. (Council for Agricultural Science and Technology (CAST), 2009)
This Commentary explores the interaction between the regulatory policy of the Endangered Species Act, public perception, and science in relation to the interpretation of risk to endangered species from various “stressors” associated with agricultural practices. In the absence of definitive government policy, courts are establishing risk mitigation procedures that may adversely affect agricultural productivity and practices. The authors address several potential remedies, including (1) better communication, (2) clear policy and agency coordination, (3) recognition and consideration of long-term impacts, and (4) balanced and consistent implementation.
Keywords: ESA; Natural Ecosystems; Endangered Species